A Cyanobacterial Gene, sqdX, Required for Biosynthesis of the Sulfolipid Sulfoquinovosyldiacylglycerol - Güler, Sinan (American Society for Microbiology, 2000)
The sulfolipid sulfoquinovosyldiacylglycerol is present in the photosynthetic membranes of plants and many photosynthetic bacteria. A novel gene, sqdX, essential for sulfolipid biosynthesis in the cyanobacterium Synechococcus sp. strain PCC7942 is proposed to encode the cyanobacterial sulfolipid synthase catalyzing the last reaction of the pathway.